2016
DOI: 10.3390/ijms17101608
|View full text |Cite
|
Sign up to set email alerts
|

Waste Soybean Oil and Corn Steep Liquor as Economic Substrates for Bioemulsifier and Biodiesel Production by Candida lipolytica UCP 0998

Abstract: Almost all oleaginous microorganisms are available for biodiesel production, and for the mechanism of oil accumulation, which is what makes a microbial approach economically competitive. This study investigated the potential that the yeast Candida lipolytica UCP0988, in an anamorphous state, has to produce simultaneously a bioemulsifier and to accumulate lipids using inexpensive and alternative substrates. Cultivation was carried out using waste soybean oil and corn steep liquor in accordance with 22 experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 60 publications
2
37
0
1
Order By: Relevance
“…Bioemulsifiers are amphiphilic compounds with a high molecular weight that have a high response to surface tension. They have a hydrophobic (amino acids, mono/disaccharide peptides, polysaccharides) and hydrophilic (saturated or unsaturated fatty acids) portion, allowing interaction with fluids of different polarities (oil/water and water/oil), the forming of microemulsions, and provide detergency, solubilizing, and emulsifying actions [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Bioemulsifiers are amphiphilic compounds with a high molecular weight that have a high response to surface tension. They have a hydrophobic (amino acids, mono/disaccharide peptides, polysaccharides) and hydrophilic (saturated or unsaturated fatty acids) portion, allowing interaction with fluids of different polarities (oil/water and water/oil), the forming of microemulsions, and provide detergency, solubilizing, and emulsifying actions [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It is also a cheap source of proteins, amino acids, minerals, vitamins, and trace elements and can be used as a rich and effective nutritional substitute for expensive complex media like beef extract, meat extract, yeast extract, and peptone in fermentation studies [12][13][14][15]. Studies have shown that CSL can be used as a nutrition supplement and a cheap nitrogen source for cellular growth in the production of some fermentation products [12,14,16]. Edwinoliver et al [14] showed that the utilization of CSL led to a reduction in the overall cost of lipase production medium by 55-60% of the total medium cost, thereby making the process economically attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, BS of fungal origin have wide application and can be used in several industrial sectors that use chemical surfactants. Such industries include: petroleum, pharmaceuticals, cosmetics, agriculture with regard to formulating herbicides and pesticides, and the production of personal hygiene products and food processing, as described by NITSCHKE; PASTORE (2002), confirmed by the literature (Table 1), and presented in Table 5 ( BANAT et al, 2000;BHARDWAJ et al, 2013;LIMA et al, 2016;SOUZA AF et al, 2016;SOUZA KST et al, 2017;AGHAJANI et al, 2018).…”
Section: Applications Of Biosurfactantsmentioning
confidence: 97%
“…However, they are excellent producers of BS or BE, as well as emulsifiers, with stable emulsions, and have an excellent capacity to reduce stress. Moreover, they promote the dispersion of hydrophobic compounds, which enables them to be applied in different sectors SOUZA AF et al, 2016;SOUZA PM et al, 2016;2017b;PELE et al, 2018). Candida antarctica Kim et al (2002) Influence of physico-chemical parameters on the production of biosurfactants or bioemulsifiers…”
Section: Introductionmentioning
confidence: 99%